Thyroid cancer in adolescents and young adults. Issue 8 (12th March 2018) - Massimino, Maura; Evans, Douglas B.; Podda, Marta; Spinelli, Claudio; Collini, Paola; Pizzi, Natalia; Bleyer, Archie
Abstract: In adolescents and young adults, thyroid cancer accounts for 13% of all invasive neoplasms, being three times more frequent in females, but overdiagnosis and overtreatment are common. There are two therapeutic approaches, one radical and no longer preferred in all instances, and the other conservative. Permanent complications of surgery and metabolic irradiation can affect quality of life and carry an economic burden. The overall survival rate approaches 100% for patients with differentiated thyroid cancer regardless of the extent of treatment. Medullary thyroid carcinoma is a very different entity, occurring most frequently in the context of hereditary tumor susceptibility syndromes.